2022
DOI: 10.1097/j.pain.0000000000002803
|View full text |Cite
|
Sign up to set email alerts
|

Chronic temporomandibular disorders are associated with higher propensity to develop central sensitization: a case–control study

Abstract: Temporomandibular disorders (TMD) include a group of musculoskeletal disorders that may involve increased responsiveness of nociceptive neurons in the central nervous system (ie, central sensitization). To test this hypothesis further, this study examined whether, as compared with healthy subjects, patients with chronic TMD have a greater propensity to develop secondary mechanical hyperalgesia-a phenomenon that can be confidently attributed to central sensitization. In this case-control study, we assessed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
(101 reference statements)
0
3
0
Order By: Relevance
“…However, in contrast with our previous findings [28] we found no effect of social support on the spread of hypersensitivity. This is another instance of a dissociation between the spread and the subjective ratings of hypersensitivity as has been found in previous studies [12,28,40,59]. While some of these studies have succeeded in modulating only the spread of hypersensitivity [12,28,40], others have only been able to modulate the subjective ratings of hypersensitivity [59].…”
Section: The Effect Of Social Support On Mechanical Hypersensitivitysupporting
confidence: 62%
See 1 more Smart Citation
“…However, in contrast with our previous findings [28] we found no effect of social support on the spread of hypersensitivity. This is another instance of a dissociation between the spread and the subjective ratings of hypersensitivity as has been found in previous studies [12,28,40,59]. While some of these studies have succeeded in modulating only the spread of hypersensitivity [12,28,40], others have only been able to modulate the subjective ratings of hypersensitivity [59].…”
Section: The Effect Of Social Support On Mechanical Hypersensitivitysupporting
confidence: 62%
“…This is another instance of a dissociation between the spread and the subjective ratings of hypersensitivity as has been found in previous studies [12,28,40,59]. While some of these studies have succeeded in modulating only the spread of hypersensitivity [12,28,40], others have only been able to modulate the subjective ratings of hypersensitivity [59]. Although both the spread and the subjective ratings are typically used as markers of hypersensitivity, it remains unclear at present, as to why the two measures are sometimes differentially modulated.…”
Section: The Effect Of Social Support On Mechanical Hypersensitivitymentioning
confidence: 52%
“…Such a dissociation between the area of SH and subjective ratings was also found by Matre et al (2006) where a placebo intervention reduced the area of SH, but not the intensity ratings [45]. A more recent study using MFS also showed that patients (vs healthy controls) with Temporomandibular Disorders developed a 76% larger area of SH, but showed no difference in the intensity of SH [15]. On the other hand, Torta et al (2022) found that an observational learning intervention attenuated subjective ratings but not the area [65].…”
Section: Effects Of Social Support On the Development Of Shmentioning
confidence: 67%
“…45 A more recent study using MFS also showed that patients (vs healthy controls) with temporomandibular disorders developed a 76% larger area of SH but showed no difference in the intensity of SH. 15 On the other hand, Torta et al (2022) found that an observational learning intervention attenuated subjective ratings but not the area. 66 Such dissociations indicate that the 2 measures may be indices of slightly different phenomena or perhaps different aspects of the same phenomenon that are influenced by different variables.…”
Section: Discussionmentioning
confidence: 99%
“…It is typically recorded as secondary mechanical hyperalgesia (SMH) or dynamic mechanical allodynia (DMA). 20 , 73 , 83 , 102 Such measurements rely on cooperation and feedback from the tested person. 42 Therefore, the measures are potentially subject to factors influencing response behaviour in the tested person, such as disposition, motivation, expectation, or interaction, with the experimenter that can vary between men and women.…”
Section: Introductionmentioning
confidence: 99%